Trials of testosterone replacement reporting cardiovascular adverse events - Gagliano-Jucá, Thiago (Asian J Androl, 2018)
The numbers of testosterone prescriptions written have increased several-fold worldwide, but the incidence of pathological hypogonadism due to hypothalamic, pituitary, and testicular disease has remained unchanged. Most of these prescriptions are being dispensed to middle-aged and older men who have experienced age-related decline in serum testosterone levels; a subset of the population in which benefits of testosterone replacement is at best, modest. Recently, some randomized controlled trials have reported increased cardiovascular events in men (mainly older men and those with prevalent cardiovascular disease) with testosterone use, and a few recent meta-analyses have confirmed these findings. In this review, we discuss trials of testosterone therapy that have reported higher cardiovascular events, relevant trials that have not reported increased cardiovascular events and large trials that have focused on cardiovascular risk (mainly atherosclerosis progression) as their main outcome. We also review findings from meta-analyses that have evaluated cardiovascular events in various testosterone trials. Finally, we discuss some potential mechanisms by which testosterone use might result in an increased cardiovascular risk. As none of the trials conducted to date were adequately powered to evaluate cardiovascular events, no firm conclusions can be drawn regarding the cardiovascular safety of testosterone therapy at this time. In the interim, we hope that this review will help practitioners make informed decisions regarding the care of their patients.